1997
DOI: 10.1143/jjap.36.3804
|View full text |Cite
|
Sign up to set email alerts
|

Structures on Si(100) 2 × 1 at the Initial Stages of Homoepitaxy by SiH 4 Decomposition

Abstract: The initial stages of homoepitaxial island formation on Si(100)2×1 by SiH4 decomposition under ultra high vacuum chemical vapor deposition conditions are studied by scanning tunneling microscopy and kinetic model calculations. The concentrations of the intermediate species formed on the surface during SiH4 decomposition are calculated from the kinetic parameters of the dissociation cascade leading to Si film growth in the temperature regime of 500 to 800 K and for SiH4 pressures in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…28 If we assume as in Mason 7 and Richardson et al 17 that H coverage prevents contaminants, such as C and O, from depositing onto the surface, but does allow Si to deposit, then at higher substrate temperatures increased hydrogen desorption leads to higher contaminant incorporation, which would increase the surface roughness with increasing substrate temperature. 13,17,29 Moreover, given that the H coverage of the Si͑100͒ surface at high H dilutions is large and temperature independent below 300°C, 30 then as we lower the substrate temperature from 270°C to 230°C, we suggest that film growth becomes surface mobility limited and there is an increase in the film roughness once more.…”
Section: A Thin Film Structure and Crystallinitymentioning
confidence: 78%
“…28 If we assume as in Mason 7 and Richardson et al 17 that H coverage prevents contaminants, such as C and O, from depositing onto the surface, but does allow Si to deposit, then at higher substrate temperatures increased hydrogen desorption leads to higher contaminant incorporation, which would increase the surface roughness with increasing substrate temperature. 13,17,29 Moreover, given that the H coverage of the Si͑100͒ surface at high H dilutions is large and temperature independent below 300°C, 30 then as we lower the substrate temperature from 270°C to 230°C, we suggest that film growth becomes surface mobility limited and there is an increase in the film roughness once more.…”
Section: A Thin Film Structure and Crystallinitymentioning
confidence: 78%
“…Much work, both theoretical and experimental, is reported in the literature about the adsorption and the successive decomposition of SiH 4 on the Si(100)−(2 × 1) surface. It was experimentally shown by Fehrenbacher et al 70, 71 that the adsorption of small silicon species does not break the surface reconstruction nor leads to surface etching. Boland 72 showed that adsorption of SiH 4 at about 700 K leads to a surface that is mainly monohydrate.…”
Section: Elementary Processesmentioning
confidence: 99%
“…Scanning tunneling microscopy (STM) studies have shown that island nucleation in SiH 4 -based ultrahigh vacuum CVD (UHV-CVD) on Si(100)-(2 × 1) depends very sensitively on the dissociation process of the SiH 4 molecule on the surface, since the kinetics of these coupled reactions determine the rate by which Si is supplied on the surface [5,6]. Additionally, surface diffusion is considerably hindered by the various hydrogen-containing species evolving on the surface from SiH 4 dissociation, which also influences island formation [7,8].…”
Section: And Sih 2 CL 2 At Intermediate Temperatures Is Illustratedmentioning
confidence: 99%